Implementing a Text-Based Approach within the K-13 Curriculum in Senior High School - Pertiwi, Agustina; Mardiah, Diah; Syahrey, Rozaqey Alvey; Hasibuan, Kalayo (Lembaga Riset dan Inovasi Almatani, 2024)
This article delves into the potential advantages of implementing a text based approach within K-13 curriculum in senior high school. It underscores the increasing importance of critical thinking and communication skills in today's educational landscape and argues that a text-based approach offers a promising avenue for enhancing the learning experience. By immersing students in a variety of texts, this method not only cultivates their communication skills but also fosters a deeper understanding of complex subjects through the analysis and interpretation of written materials. Students who actively engage with diverse texts and hone their analytical and critical thinking abilities are better prepared to meet the challenges of both the workforce and higher education. Furthermore, the article contends that by incorporating a text-based approach into the K–13 curriculum, senior high school students can be equipped with the necessary tools for future success. This approach not only empowers students to navigate academic and professional environments with confidence but also nurtures their intellectual growth and adaptability. Ultimately, the article advocates for the adoption of a text-based curriculum as a means of fostering holistic development and preparing students for the multifaceted demands of the 21st-century world.